Additive manufacturing of WMoTaTi refractory high-entropy alloy by employing fluidised powders. (20th October 2022) - Liu, Chang; Zhu, Keyan; Ding, Wangwang; Liu, Yu; Chen, Gang; Qu, Xuanhui
ABSTRACT : In this study, WMoTaTi refractory high-entropy alloy was successfully fabricated via selective laser melting (SLM) using pre-alloyed powders by mechanical milling combined with gas–solid fluidisation. Fluidisation effectively improves the particle sphericity and thus its spreading performance suitable for SLM. Processing parameters were investigated in terms of laser power, hatching space and scanning rate. The relative density of WMoTaTi made by SLM (SLMed) reaches 95.8 ± 1.4%, and it consisted of dominant BCC phase and minor HCP phase. The slight precipitation of HCP Ti was driven due to the non-equilibrium solidification during ultra-rapid cooling by SLM. The microhardness of WMoTaTi via SLM is 617.2 ± 4.1 HV, preferable to those fabricated by traditional manufacturing processes. The sound microhardness is resulted from the fine grain size and nano-sized HCP precipitates, which favour dislocation pinning and promote strength. This work demonstrates that SLMed WMoTaTi has sound mechanical properties while using the cost-affordable pre-alloyed powders by fluidisation.